Produção de hidrogênio e metano a partir da co-digestão de soro de queijo e glicerol em reator anaeróbio de leito fluidizado - Almeida, Priscilla de Souza (2021)
Cheese whey and glycerol are by-products of the dairy and biodiesel industry, respectively. Both by-products are highly produced and can be used in the anaerobic digestion process for energy generation due to their high organic content. The adoption of two-stage anaerobic digestion associated with the application of co-substrates brings several advantages, such as increases in COD removal and production of H2 and CH4. In this context, the objective of this research was to evaluate the co-digestion of cheese whey and glycerol in an anaerobic fluidized bed reactor (AFBR) using a two-stage process, and to verify the effect of organic loading rate (OLR) and temperature on the production of H2 and CH4. Thus, the co-digestion was performed in a thermophilic methanogenic reactor (RU-T) by increasing the OLR from 2 to 20 gCOD.L-1.d-1, with a hydraulic retention time (HRT) of 24 h. After the optimal concentration determination, the HRT was decrease from 24 to 20 and 16 h. For the two-stage process, the OLR of the acidogenic reactor (RA-T) was increased from 60 to 120 gCOD.L-1.d-1 (HRT 4 h) and of the methanogenic reactor from 2 to 20 gCOD.L-1.d-1 (HRT 24 h). Besides, the effect of temperature was investigated in the second stage using a thermophilic (RS-T) and a mesophilic (RS-M) methanogenic reactor. RU-T showed the best performance in the OLR of 10 gCOD.L-1.d-1, with methane yield (MY) of 253.0 NmL CH4.gCOD-1rem and methane production rate (MPR) of 3.2 L CH4.L-1.d-1. In the HRT evaluation, the HRT of 20 h provided the maximum MY of 292.5 NmL CH4.gCOD-1rem, while the maximum MPR was observed in the HRT of 16 h (5.1 L CH4.L-1.d-1). Acetic and propionic acid were the dominant metabolites. Regarding the two-stage process, the RA-T provided a yield of 1.7 mmol H2.gCOD-1app and hydrogen production rate of 3.9 L H2.L-1.d-1, both in the OLR of 90 gCOD.L-1.d-1, with butyric and acetic acid as main metabolites. RS-M produced the highest MY and MPR, equal to 273.2 NmL CH4.gCOD-1rem and 5.8 L CH4.L-1.d-1 in the OLR of 20 gCOD.L-1.d-1. The RS-T showed MY of 269.9 NmL CH4.gCOD-1rem in OLR 10 gCOD.L-1.d-1 and MPR of 4.4 L CH4.L-1.d-1 in 20 gCOD.L-1.d-1. Acetic and isobutyric acid were the main metabolites. Through sequencing analysis, was identified as dominant genus in RA-T Themoanaerobacterium. Archaeas of the genus Methanobacterium was the most abundant in RS-M and RU-T, while the genus Methanothermobacter was in RS-T. In general, it is verified that OLR above 10 gCOD.L-1.d-1 was harmful to RU-T and RS-T, while RS-M showed stability at 20 gCOD.L-1.d-1. The two-stage process showed better performance, however, considering the results of the HRT evaluation in the RU-T, there is the possibility of applying smaller HRT in the second stage for higher CH4 production.